(untitled) (Contemporary Journal of Social Science Review, 2025)
Introduction The trend of using Artificial Intelligence (AI) more in marketing is transforming businesses approaches particularly when it comes to Small and Medium-sized Enterprises (SMEs) in new economies. Although big companies have taken advantage of AI, to refine their marketing approaches, SMEs are forced to struggle a great deal to embrace the technologies. The paper will discuss the application of AI in marketing and its implications on the performance of businesses within the SMEs in the developing economies. Objective The key concept of the study is to consider the extent of adoption of AI in the marketing operations, the perceived benefits, challenges faced during adoption and the consequential impact to the business success of SMEs. The paper also analyses how strategic preparedness can facilitate the application of AI technologies to incorporate them. Methodology It was also conducted using a quantitative research design whereby a survey questionnaire based on a structured questionnaire was utilized and conducted on 250 respondents who represented various SMEs. The significant constructs, including AI adoption, its perceived advantages, implementation obstacles, business success, and future readiness were evaluated as well in the survey. The data was analyzed using the descriptive statistics, correlation analysis, regression, and one-way ANOVA to establish the correlation between AI adoption and the business results. Results It happened that the introduction of AI is positively correlated with the success of the business, and the perceived benefits can have a significant impact on the enhancement of marketing performance and efficiency. However, the study also outlines several barriers to AI adoption such as financial limitations, lack of knowledge and infrastructure related challenges that make SMEs unable to make the most out of AI technologies. It turned out that future readiness is also a predictor of a successful AI integration, and the pro-active strategic plan including the training of employees is the key to surmounting the challenges encountered with the implementation process. Conclusion AI application in the marketing sector is capable of significantly improving the performance of the business of the SMEs in the emerging economies. However, the problems that are related to the limited number of resources, technical complexity, and the lack of strategic preparedness should also be addressed so that to take the best out of AI. The study recommends SMEs to be keen on building a solid digital infrastructure, investing in employee training, and aligning AI activities with definite business objectives to ensure that AI-based marketing strategies can be as efficient as possible.